Outward FDI does not necessarily cost domestic employment of MNEs at home: Evidence from Japanese MNEs - In Hyeock Lee; Shige Makino; Eunsuk Hong (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2015)
Outward FDI does not necessarily reduce domestic employment – it often boosts it. Evidence from Japanese MNEs show that they increase domestic employment in Japan when they conduct market-seeking, strategic asset-seeking, or efficiency-seeking FDI to expand domestic operations into foreign countries, and hence enhance their competitive advantages.
Keywords: 330